Ammonium hydroxide as the ultimate amino source for the synthesis of N-unprotected 3-tetrasubstituted aminooxindoles via catalyst-free direct amination. Issue 6 (10th March 2020) - Yue, Jing; Ma, Xi-Tao; Liu, Xiong-Li; Wang, Jun-Xin; Liu, Xiong-Wei; Zhou, Ying
Abstract : The direct use of ammonium hydroxide in amination for the synthesis of primary amines is considered to be one of the major challenges in synthetic organic chemistry. Abstract : The direct use of ammonium hydroxide in amination for the synthesis of primary amines is considered to be one of the major challenges in synthetic organic chemistry. Herein, the first example of catalyst-free direct amination of 3-halooxindoles with ammonium hydroxide to synthesize N -unprotected 3-tetrasubstituted aminooxindoles in high yields (up to 91% yield) is described. An enhancement of the reaction rate on using water was observed under mild conditions. Such an approach is not only protection/deprotection-free, but also more practical and cost-effective. Moreover, this method could expand the library of 3-tetrasubstituted aminooxindole building blocks for the further synthesis of AG-041R, GHSR antagonists and a charteline unit, opening up a new synthetic pathway in the chemistry of 3-aminooxindoles.